The grammar of criminal law : - Fletcher, George P. (Oxford University Press, 2007)
The Grammar of Criminal Law is a 3-volume work that addresses the field of international and comparative criminal law, with its primary focus on the issues of international concern, ranging from genocide, to domestic efforts to combat terrorism, to torture, and to other international crimes. The first volume is devoted to foundational issues. The Grammar of Criminal Law is unique in its systematic emphasis on the relationship between language and legal theory; there is no comparable comparative study of legal language. Written in the spirit of Fletcher's classic Rethinking Criminal Law, this work is essential reading in the field of international and comparative law